Formation of Bi2Sr2CaCu2Ox/Ag multifilamentary metallic precursor powder-in-tube wires. (12th October 2016) - Zhang, Yun; Koch, Carl C; Schwartz, Justin
Abstract: Previously, a metallic precursor (MP) approach to synthesizing Bi2 Sr2 CaCu2 O x (Bi2212), with a homogeneous mixture of Bi, Sr, Ca, Cu and Ag was produced by mechanical alloying. Here, Bi2212/Ag round multifilamentary wire is manufactured using a metallic precursor powder-in-tube (MPIT) process. The MP powders were packed into a pure Ag tube in an Ar atmosphere and then sealed. After deformation, multifilamentary round wires and rolled tapes were heat treated in flowing oxygen through three stages: oxidation, conversion and partial-melt processing (PMP). Processing-microstructure-property relationships on 20–50 mm long multifilamentary round wires and rolled tapes were studied extensively. It is shown that conventional wire deformation processes, optimized for oxide-powder-in-tube wires, are not effective for deforming MPIT wires, and that as with prior studies of MPIT Bi2 Sr2 Ca2 Cu3 O y conductors, hot extrusion is required for obtaining a multifilamentary structure with fine filaments. As a result, the Bi2212 MPIT wires reported here have low engineering critical current density. Nonetheless, by focusing on sections of wires that remain intact after deformation, it is also shown that the first heat treatment stage, the oxidation stage, plays a crucial role in chemical homogeneity, phase transformation, and microstructural evolution and three reaction pathways for MP oxidation are presented. Furthermore, it is found the Bi2212 grain alignment within an MPIT filament is significantly different from that found in OPIT filaments after PMP, indicating the formation of highly dense filaments containing Bi2212 fine grains and Ag particles before PMP aids the formation of large, c -axis textured Bi2212 filaments during PMP. These results show that, with improved wire deformation, high critical current density may be obtained via a MPIT process.